Synthesis of Polymer Assembled Mesoporous CaCO3 Nanoparticles for Molecular Targeting and pH-Responsive Controlled Drug Release - Jinjing Xing; Yeqiang Cai; Yikun Wang; Haifu Zheng; Yujia Liu (Advances in Polymer Technology)
CaCO3 nanoparticles are very suitable as intelligent carriers because of their ideal biocompatibility and biodegradability, especially their sensitivity to pH. In this paper, we use mesoporous CaCO3 nanoparticles as intelligent carrier, sodium alginate, and chitosan as alternating assembly materials, folic acid as target molecules, and exploit layer-by-layer assembly technology to achieve sensitive molecular targeting and pH response drug release. Mesoporous CaCO3 hybrid nanoparticles have high drug loading on doxorubicin. The effects of different pH values on drug release in vitro were studied by regulating simulated body fluids with different pH values. The cytotoxicity, targeting effect, and drug release of human cervical cancer cell line (HeLa) were studied by cell vitality and imaging experiments. All the evidence suggests that the smart mesoporous CaCO3 nanoparticles may be a potential clinical application platform for cancer therapy.